Long peripheral catheters in children: A scoping review. Issue 12 (27th September 2022) - Burek, Alina G.; Liljestrom, Tracey; Dundon, Melanie; Shaughnessy, Erin E.; Suelzer, Elizabeth; Ullman, Amanda
Abstract: Background and Objectives: Long peripheral catheters (LPCs) are emerging vascular access devices used for short‐medium term vascular access needs. Literature in adults suggests LPCs have longer dwell‐times than peripheral intravenous catheters (PIVs) and lower rates of serious complications than peripherally inserted central catheters (PICCs). The role of LPCs in children is less established. The objective of this scoping review is to describe and synthesize the existing literature on the effectiveness and safety of LPCs in children. Methods: This review follows the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses extension for Scoping Reviews (PRISMA‐ScR) guidelines. Searches were done in MEDLINE (Ovid), Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science Core Collection, Scopus, CINAHL (Ebsco), and Google Scholar most recently on February 22, 2022. Studies were included if published in English on or after 2000 and included patients <18 years of age. Results: Twenty‐one studies were included. The body of literature is variable in quality, measurements, and reported outcomes. Median dwell‐time ranged from 5 to 14 days. The rate of completion of therapy ranged from 20% to 86%. Dislodgement, occlusion, and infiltration were the most common complications reported (0%–31%). Venous thromboembolism rates ranged from 0% to 13%. The rate of catheter‐related bloodstream infection was 0% in 9 of 10 studies. Less than 50% of studies reported comparative outcomes. Conclusion: LPCs show promising outcomes in select populations, with longer dwell‐time than PIVs and possibly lower rates of serious complications than PICCs. However, more research is needed to clarify the optimal use of LPCs in pediatrics.